Different concentrations and solubility of active lime (CaCO3) on the quality of indigo paste from Indigofera longiracemosa Boiv.ex. Baill - Muzzazinah; Azmi, Hilmi Uulul (Jurnal Rekayasa Proses, 2025)
This research aims to determine the effect of differences in concentration and solubility of active lime (25% and 35% CaCO3 solution, 25% and 35% CaCO3 supernatant) on the quality of indigo (Indigofera longiracemosa) dye paste. The method for making indigo dye paste includes the process of soaking fresh leaves and twigs of I. longiracemosa in water, fermentation with an active lime solution of CaCO3 with varying concentrations and solubility, settling, and filtration to obtain indigo paste. Several tests were carried out to evaluate the quality of the color in the fabric and the indican content in the indigo produced. The indican content that was successfully tested showed the highest results in the paste treated with 25% CaCO3. Color quality tests on fabrics show that fabrics dyed with indigo paste with 35% CaCO3 solution treatment have the best color fastness to sweat with an average value of 4. The color fastness test to heat on fabric dyed with indigo paste with all types of treatment received a score of 4-5, which indicates excellent color fastness, does not fade, and does not stain other fabrics. The differences in concentration and solubility of CaCO3 solution result in variations in the physical characteristics of indigo paste, the colors produced on fabric, the indican content, as well as the colorfastness to sweat and heat.